VALIDITY AND EFFECTIVENESS OF ETHNOSCIENCE-BASED CHEMISTRY LEARNING MATERIALS ON REDOX AND CHEMICAL NOMENCLATURE TO ENHANCE STUDENTS’ SCIENTIFIC LITERACY AND CRITICAL THINKING SKILLS - Wahyuni, Sri; Novita, Mega; Hayat, Muhammad Syaipul (Jurnal pendidikan matematika dan IPA (Online), 2025)
This study aims to develop and test the validity and effectiveness of ethnoscience-based chemistry learning devices on redox material and chemical compound nomenclature to improve science literacy and critical thinking skills of students. This research uses the 4D development model (Define, Design, Develop, Disseminate). The learning devices developed include teaching modules, learning materials, and student worksheets. The research subjects were 34 class XII students at MAN Wonogiri. The findings show that: (1) The learning devices were declared very valid by expert validators with scores of 91.15% for teaching modules, 91.82% for LKPD, 93.20% for teaching materials, and 22.5 (scale 25) for question instruments, (2) Practitioner validators also declared the devices very valid with scores of 90.72% for teaching modules, 92.73% for LKPD, 94.00% for teaching materials, and 23.5 (scale 25) for question instruments, (3) The reliability and validity tests showed Cronbach Alpha values of 0.749 and 0.921 for science literacy and critical thinking instruments respectively, (4) The learning devices are effective with N-gain values of 0.6103 for science literacy and 0.6501 for critical thinking skills, both in moderate category. The ethnoscience-based learning tools developed are valid and effective to improve students' science literacy and critical thinking skills.